Psychological stress and psoriasis: a systematic review and meta‐analysis. (1st May 2018) - Snast, I.; Reiter, O.; Atzmony, L.; Leshem, Y.A.; Hodak, E.; Mimouni, D.; Pavlovsky, L.
Summary: Background: Psychological stress has long been linked with the exacerbation/onset of psoriasis. Objectives: To determine if antecedent psychological stress is associated with the exacerbation/onset of psoriasis. Methods: A search of the PubMed, PsycINFO, Cochrane library and ClinicalTrials.gov databases was performed. Surveys evaluating beliefs about stress reactivity were analysed separately. Suitable studies were meta‐analysed. Results: Thirty‐nine studies (32 537 patients) were included: 19 surveys, seven cross‐sectional studies, 12 case–control studies and one cohort study. Forty‐six per cent of patients believed their disease was stress reactive and 54% recalled preceding stressful events. Case–control studies evaluating stressful events rates prior to the exacerbation ( n = 6) or onset ( n = 6) of psoriasis varied in time lag to recollection (≤ 9 months to ≥ 5 years). Pooling five studies evaluating stressful events preceding onset of psoriasis gave an odds ratio (OR) of 3·4 [95% confidence interval (CI) 1·8–6·4; I 2 = 87%]; the only study evaluating a documented stress disorder diagnosis reported similar rates between patients and controls (OR 1·2, 95% CI 0·8–1·8). Four studies evaluating stressful events prior to psoriasis exacerbation reported comparable rates with controls, whereas two found more frequent/severe preceding events among patients with psoriasis. A small prospective cohort study reported a modest association between stress levels and exacerbation of psoriasis ( r = 0·28, P < 0·05). Conclusions: The association between preceding stress and exacerbation/onset of psoriasis is based primarily on retrospective studies with many limitations. No convincing evidence exists that preceding stress is strongly associated with exacerbation/onset of psoriasis.